Characteristic of Сells' Reaction of APUD-System of Guinea Pigs as Marker of Adaptive-Compensatory Processes under Aerogenic Immunization against Plague - S. A. Bugorkova; S. Yu. Zadumina; S. A. Piontkovskiy; T. V. Bugorkova; L. V. Samoylova (Проблемы особо опасных инфекций, 2010)
Carried out was morphometric analysis of cells' reaction of APUD system (neuroendocrinal cells) of guinea pigs immunized with live plague vaccine by aerogenic method. The results of investigations were compared with characteristics of the state of biomodel's internal organs. Elucidated was that the changes of morphofunctional state of neuroendocrinal cells in lungs and organs of immunity were of phase character suggesting the involvement of APUD system elements in the inhalant method of antigenic material intake. Assessment of APUD-system cell's reaction enables to estimate indirectly the nature of adaptive and compensatory processes in biomodel in the course of anti-plague vaccination.